A numerical investigation of support structure designs for overhangs in powder bed electron beam additive manufacturing. (January 2020) - Cheng, Bo; Chou, Kevin
Highlights: A numerical model is utilized to investigate the thermomechanical phenomenon in EBAM process for novel overhang support designs. The simulated overhang deformation was qualitatively similar to that of the experimentally fabricated sample. Overhang deformation can be reduced by the application of a heat support in powder bed and support anchors which connect overhang and heat support. Abstract: Overhang structures can be found in engineering components fabricated by powder bed electron beam additive manufacturing (EBAM) technology. The support structures are needed for an overhang, or severe overhang distortion may be caused by repeated rapid heating and cooling cycles in the layer-by-layer manufacturing process. Current overhang support generation methods usually utilize certain types of structures to fill the overhang space. They may overestimate the amount of support, thus, the post process time can be potentially increased. The objective of this study is to investigate an effective support design method to reduce support material usage and post process workload in EBAM process. In this research, a combined heat support and support anchor design method has been proposed. The stress and deformation of overhang configuration has been evaluated by a thermomechanical model. The design procedure has been introduced in details for a typical overhang example. The simulations have demonstrated that overhang warping can be effectively reduced by the application of a heat support beneath overhang region and support anchors which connect overhang and heat support.